Detecting, Analyzing and Understanding Zero- Transfer Attacks in the Ethereum Ecosystem - Kotidis, Leonidas (My University, 2025)
This thesis looks into zero-transfer attacks on the Ethereum blockchain which is a type of scam where attackers trick users into sending money to the wrong wallet by sending fake, zero-value transactions. While the general idea of these attacks is known, its not widespread and there hasn’t been much largescale research to show how often they happen or how to detect them effectively. To fix that, we built a Python framework using Selenium to collect wallet data directly from Etherscan. We scraped over 18,000 real user wallet histories and filtered out exchanges or non-wallet addresses. Then we parsed every transaction to pull info like wallet addresses, timestamps, amounts, and transaction IDs. We designed two versions of a detection method, one relaxed and one strict. The relaxed version flagged more possible attacks, but had more false positives. The strict version added checks for both the first and last four characters of the wallet address and only flagged transactions under $2 to improve accuracy. On the strict version in total, 3.96% of wallets had been targeted, and over 11,600 attacks were detected. Of these, 1,205 were successful, though most only led to small losses. The results show that while these attacks don’t bring big profits most of the time, they rely on volume. Attackers hope that eventually, someone makes a big mistake. Overall, the detection method worked well and can be a solid base for building tools to help users stay safe.
Keywords: zero-transfer attacks; Ethereum blockchain; attackers trick users; zero-value transactions